Low complexity multiuser detection algorithm for CDMA systems - Li, Zhongjie (2008)
This research is emphasized on the study of low complexity multiuser detection algorithms for code-division multiple-access (CDMA) communications systems. Three efficient detectors are proposed in this thesis. These detectors include the weighted polynomial expansion (WPE) detector, the blind cascaded modular detector and the blind RAKE structure cascaded modular detector. The WPE detector can effectively approximate the decorrelating detector and MMSE detector. The blind cascaded modular detector is proposed to implement the blind minimum output energy (MOE) detector. The detector is relatively simple and has a low complexity compared with conventional blind MOE detectors. The RAKE structure cascaded modular detector has been proposed to handle the signature mismatch problem in DS-CDMA system over multipath fading channel. The detector does not require the knowledge of the fading channel and can achieve good performance with a simple structure compared with other blind receivers that need to estimate the channel information.